Uncovering deformation processes from surface displacements. (December 2016) - Stramondo, Salvatore; Trasatti, Elisa; Albano, Matteo; Moro, Marco; Chini, Marco; Bignami, Christian; Polcari, Marco; Saroli, Michele
Abstract: Today, satellite remote sensing has reached a key role in Earth Sciences. In particular, Synthetic Aperture Radar (SAR) sensors and SAR Interferometry (InSAR) techniques are widely used for the study of dynamic processes occurring inside our living planet. Over the past 3 decades, InSAR has been applied for mapping topography and deformation at the Earth's surface. These maps are widely used in tectonics, seismology, geomorphology, and volcanology, in order to investigate the kinematics and dynamics of crustal faulting, the causes of postseismic and interseismic displacements, the dynamics of gravity driven slope failures, and the deformation associated with subsurface movement of water, hydrocarbons or magmatic fluids.